Automation and Low-Skill Labor - Katja Mann; Dario Pozzoli (Institute of Labor Economics (IZA), 2022)
Changes in the supply of low-skill labor may affect robot adoption by firms. We test this hypothesis by exploiting an exogenous increase in the local labor supply induced by a large influx of immigrants into Danish municipalities. Using the Danish employer-employee matched dataset over the period 1995-2019, we show in a shift-share regression that a larger share of migrants in a municipality leads to fewer imports of robots at the firm-level. We rationalize this finding in a simple model of robot adoption in which robots and low-skill workers are substitutes. As many advanced economies are facing labor shortages, this paper sheds light on the future of robotization.
Keywords: E22; J20; J61; R23; 330; labor supply; immigration; robots; shift-share